City Managers Have Ethics Too? Comparing Planning and City Management Codes of Ethics. Issue 2 (3rd April 2017) - Johnson, Bonnie J.; Peck, Mary Kay; Preston, Steven A.
Abstract : Problem, research strategy, and findings : Planners and city and county managers regularly work together but often face ethical conundrums. We compare the codes of ethics from their two U.S. professional organizations—the American Institute of Certified Planners (AICP) and the International City/County Management Association (ICMA)—and then apply the AICP Code of Ethics to five published ICMA ethics scenarios to determine how the two professions might respond differently in each. We find common professional values in the codes: equality, creativity, and diligence. The AICP Code, however, emphasizes direct democracy and engaging citizens, while the ICMA Code emphasizes representative democracy and engaging elected officials. Code values and actual behaviors are not always related, but we believe our work shows the source of ethical challenges and power struggles between managers and planners. Takeaway for practice : Planners can learn from ICMA's Code to focus on elected officials. Managers can learn from AICP's Code to focus on citizens. Planners and managers can overcome their professional biases and blind spots by understanding the ethical codes under which the other profession operates. Planners work from the outside in, managers from the inside out; working together, they can improve the communities they serve.